Avaliação da cobertura do exame de papanicolaou e seus fatores determinantes em capital brasileira de elevada incidência de câncer de colo de útero - Martin, Cibelli Navarro Roldan (2014)
Cancer of the cervix (cervical cancer) is the malignant neoplasm of the epithelial cells of the uterine cervix associated with infection by the human papillomavirus (HPV). Despite its being the cancer with the highest prevention potential, 530,000 new cases are diagnosed each year worldwide. Considering only young women, it has become the leading cause of cancer death in Brazil. The State of Roraima records the highest incidence rate of this neoplasm in the country: 28/100,000 women in 2009. The efforts of the Ministry of Health to fight this disease have focused on prevention policy. The different personal reasons for not undergoing the examination reinforce the importance of studies on screening coverage and its determinants in each region. The purpose of the study is to assess the coverage of the screening program for cervical cancer in the city of Boa Vista / State of Roraima and highlight the factors related to non-adherence to the prevailing health care model. A household survey (quantitative, cross-sectional research) was conducted to assess the prevalence of women between 25 and 59 years of age covered by the cervical cancer tracking program and collect individual information. Areabased (census) data were analyzed as explanatory variables. The cluster sampling method was used. The study was approved by the Ethics Committee of the Federal University of Roraima and 603 women were included in the survey. Five hundred and seven women (with an average age of 38.2 years) underwent the preventive examination in the past three years, with a prevalence of 85.7%. The average per capita nominal income above R$ 1,000.00 and recent medical check-up have been shown to reduce the rate of not undergoing the examination in a multivariate analysis. Of the 86 women had never undergone the examination, 65 (75.6%) did not answer why. One can observe a weak inversely proportional correlation, though statistically significant, between average nominal income and non-adherence to the screening program. We conclude that the coverage informed by the volunteers was high, compared to the coverage of more developed states in the country, suggesting some other reason (e.g.: specimen quality, follow-up loss, difficulty in treating premalignant lesions) to explain the high incidence of cervical cancer in Roraima.